Historic center regulations: definition and safeguarding of urban heritage. Case of the city of Tepic, Nayarit, Mexico - De la Torre Dávalos, Alexis Antonio (2024)
In several countries, the concept of the historic center has positioned itself at the forefront for the protection of urban heritage. However, it is interpreted and defined according to the needs and expectations of the present. Thus, the article postulates the objective of analyzing the normative framework around the historic center for the definition and safeguarding of urban heritage, based on the case of the city of Tepic, Nayarit, Mexico. It is established a methodology that starts from the analysis at the level of federal and state legislation that closes with the municipal plans and regulations. It is concluded that the normative interpretation of Mexican cultural heritage is not shared by the different levels of government, generating conflicts that directly affect the particular material and spatial configuration of historical centers.